Amniotic fluid erythropoietin and neonatal outcome in pregnancies complicated by intrauterine growth restriction before 34 gestational weeks. (6th January 2015) - Seikku, Laura; Rahkonen, Leena; Tikkanen, Minna; Hämäläinen, Esa; Rahkonen, Petri; Andersson, Sture; Teramo, Kari; Paavonen, Jorma; Stefanovic, Vedran
Abstract Objective High amniotic fluid erythropoietin concentration reflects chronic fetal hypoxia. Our aim was to study amniotic fluid erythropoietin concentration in relation to neonatal outcome in pregnancies complicated by intrauterine growth restriction. Design Retrospective case series. Setting Helsinki University Hospital, Finland. Sample A total of 66 singleton pregnancies complicated by intrauterine growth restriction. Methods Amniocentesis or amniotic fluid sampling at cesarean section was performed between 24 and 34 gestational weeks. Values of amniotic fluid erythropoietin were quantitated with immunochemiluminometric assay. Normal amniotic fluid erythropoietin was defined as <3 IU/L, intermediate as 3–27 IU/L, and abnormal as >27 IU/L. Main outcome measures Adverse neonatal outcome. Results Abnormal biophysical profile and reversed end‐diastolic flow in umbilical artery were associated with abnormal amniotic fluid erythropoietin (p < 0.001 and p = 0.042, respectively). Abnormal amniotic fluid erythropoietin was not associated with absent end‐diastolic flow in umbilical artery or with oligohydramnios (p = 0.404 and p = 0.080, respectively). Decreased umbilical artery pH and base excess values were associated with abnormal amniotic fluid erythropoietin (p = 0.027 and p = 0.007, respectively). Composite adverse neonatal outcome defined as intraventricular hemorrhage, periventricular leukomalacia, cerebral infarction and/or necrotizing enterocolitis was associated with abnormal amniotic fluid erythropoietin (p < 0.001). Conclusions High amniotic fluid erythropoietin concentrations are associated with decreased umbilical artery pH and base excess and with adverse neonatal outcome in pregnancies complicated by intrauterine growth restriction before 34 gestational weeks. In selected pregnancies complicated by intrauterine growth restriction, determining amniotic fluid erythropoietin could be a useful additional tool in fetal surveillance and possibly in optimizing timing of delivery.